2021
DOI: 10.7717/peerj.10599
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 mortality in cancer patients: a report from a tertiary cancer centre in India

Abstract: Background Cancer patients, especially those receiving cytotoxic therapy, are assumed to have a higher probability of death from COVID-19. We have conducted this study to identify the Case Fatality Rate (CFR) in cancer patients with COVID-19 and have explored the relationship of various clinical factors to mortality in our patient cohort. Methods All confirmed cancer cases presented to the hospital from June 8 to August 20, 2020, and developed symptoms/radiological features suspicious of COVID-19 were tested… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(83 citation statements)
references
References 21 publications
(29 reference statements)
6
71
6
Order By: Relevance
“…Higher age and altered sensorium at presentation is a predictor of mortality in our series. Our finding is similar to previous studies [5,7] which showed advanced age as a predictor of worse outcome. Altered sensorium has not been the clinical presentation in most series and thus a relation to it has not been inferred in existing data.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Higher age and altered sensorium at presentation is a predictor of mortality in our series. Our finding is similar to previous studies [5,7] which showed advanced age as a predictor of worse outcome. Altered sensorium has not been the clinical presentation in most series and thus a relation to it has not been inferred in existing data.…”
Section: Discussionsupporting
confidence: 93%
“…This series is a snapshot of clinical profile of these severe cases. Previous studies have shown a lower percentage of cancer patients developing severe events [2][3][4][5][6][7][8]. The main reasons for the discrepancy can be attributed to variation in the strain affecting this cohort of patients and also variation in study populations.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The first case of COVID-19 infection among the HCWs of our Institute was reported on May 1, 2020. The suspicious cases for COVID-19 were investigated by real-time polymerase chain reaction test and/or cartridge-based nucleic acid amplification test from a combination of naso-oropharyngeal swabs for SARS-CoV-2 as described previously 6 and/or by Standard Q Covid-19 Ag test following the latest national guidelines of Indian Council of Medical Research and international regulations. The laboratory confirmed COVID-19 positive HCWs during five months (May 1, 2020 to September 30, 2020) were included in the study.…”
Section: Methodsmentioning
confidence: 99%